2020
DOI: 10.3389/fpsyt.2020.00826
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ketamine Administration on Auditory Information Processing in the Neocortex of Nonhuman Primates

Abstract: Ketamine, an N-methyl-D-aspartate (NMDA) receptor antagonist, exerts broad effects on consciousness and perception. Since NMDA receptor antagonists induce cognitive impairments, ketamine has been used for translational research on several psychiatric diseases, such as schizophrenia. Whereas the effects of ketamine on cognitive functions have been extensively studied, studies on the effects of ketamine on simple sensory information processing remain limited. In this study, we investigated the cortex-wide effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Auditory responses observed from other channels provide some evidence to support the latter explanation, although electrode spacing is too large to provide a more comprehensive analysis of tonotopy. A study with very similar methods demonstrated sensitivity to different frequency tones in different subjects ( Komatsu and Ichinohe, 2020 ), which may be accounted for by the precise location of recording electrodes in relation to tonotopically sensitive regions of the auditory cortex. Analysis of auditory responses to ascending versus descending frequency transitions in the roving oddball sequence indicates that this plays a central role in shaping MMN-like response morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auditory responses observed from other channels provide some evidence to support the latter explanation, although electrode spacing is too large to provide a more comprehensive analysis of tonotopy. A study with very similar methods demonstrated sensitivity to different frequency tones in different subjects ( Komatsu and Ichinohe, 2020 ), which may be accounted for by the precise location of recording electrodes in relation to tonotopically sensitive regions of the auditory cortex. Analysis of auditory responses to ascending versus descending frequency transitions in the roving oddball sequence indicates that this plays a central role in shaping MMN-like response morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Their published findings identify an MMN-like response between 50 and 120 ms post-stimulus, providing a basis for the development of the common marmoset as a model of MMN. Mechanisms underlying this response were not discussed at length, although experiments to investigate its potential relationship with NMDA receptor function were proposed; research which has since made progress ( Komatsu and Ichinohe, 2020 ). The authors did not express consideration for alternative explanations for the observed MMN-like response, briefly stating that it conveys information regarding violation of a regularity with the auditory input stream ( Komatsu et al, 2015 ), which is generally in-keeping with the prevailing theoretical interpretation of MMN ( Fitzgerald and Todd, 2020 , Ross and Hamm, 2020 ).…”
Section: Introductionmentioning
confidence: 99%